Management of unusual missed diagnosis of a Intra-orbital wooden foreign body: A case report and review of literature. (July 2022) - Pandit, Kamal; Sitaula, Sanjeeta; Shrestha, Gulshan Bahadur; Joshi, Sagun Narayan; Chaudhary, Meenu
Abstract: Introduction: Although intra-orbital foreign bodies (IOrFBs) are commonly seen in daily ophthalmology practice, rarely, they can have very unusual clinical presentations, especially nonmetallic FBs. Presentation of case: A 33-year-old male presented with sudden onset right lower lid swelling and tearing. He was initially tolerating the symptoms, however, it got progressively worse, so he came two weeks after the initiation of symptoms. His eye vitals were within normal limit, including the visual acuity of 6/6 OU. Additionally, slit lamp and fundus examinations were benign. Concern was for infectious etiology with unclear source. After a lengthy conversation, he recalled falling on the ground with face down about 16 months ago. However, he stated that he had remained asymptomatic and never went for treatment after the incident. Non-contrast CT of head and orbit showed hyperdense tract in medial aspect of right eye adjacent to the globe, piercing across the bilateral ethmoidal sinuses. Thus, a diagnosis of retained IOrbFB was made. He underwent surgery where a 5cm rotten wood was extracted. Post-surgical course was uncomplicated. Not all penetrating intra-orbital foreign bodies present immediately after the incident. In our case the patient remained asymptomatic for 16 months. Conclusion: Therefore, when dealing with an ocular infection of unclear source, clinicians should ask about distant histories of ocular or facial injuries to assess intraocular foreign bodies. Highlights: Recognizing retained orbital foreign bodies secondary to trauma can be a challenge. Organic IOrbFB following a penetrating injury can remain asymptomatic for a significant period, resulting in delayed diagnosis and treatment. When dealing with an ocular infection of unclear source, clinicians should ask about distant histories of ocular or facial injuries to assess intraocular foreign bodies.